Prevalence of anemia in renal insufficiency among HIV infected patients initiating ART at a hospital in Northeast Ethiopia. Issue 1 (December 2017) - Fiseha, Temesgen; Tamir, Zemenu; Seid, Abdurahaman; Demsiss, Wondmagegn
Abstract Background Anemia is a strong predictor of mortality and poor quality of life among persons with either renal impairment or HIV infection. In this study, we investigated the prevalence of anemia and its association with renal insufficiency among HIV infected patients initiating ART at a hospital in Northeast Ethiopia. Methods In this retrospective cohort study, records of 373 patients on ART were selected in Dessie Referral hospital, South Wollo, Northeast Ethiopia from September 2010 to August 2013. Socio-demographic and clinical characteristics of the study patients were collected using standardized data extraction instrument. The abbreviated 4-variable Modification of Diet in Renal Disease (MDRD) study equation was used to estimate renal function (GFR) from serum creatinine. SPSS version 20.0 statistical software was used for data analysis. Results The prevalence of anemia at the time of ART initiation was 34.4%; with 20.5, 12.3 and 1.6% mild, moderate and severe anemia, respectively. Renal insufficiency was present in 27.9% of patients and was associated with a high prevalence of anemia (74%). The prevalence of anemia increased with stage of insufficiency, from 23.7% in stage 1 to 100% in stage 4. Impaired renal function (eGFR < 60 mL/min/1.73 m2 ) was associated with a higher risk of all forms of anemia; i.e., mild (AOR = 3.96; 95% CI: 2.76–5.69), moderate (AOR = 2.21; 95% CI: 1.16–4.19) and severe anemia (AOR = 5.89; 95% CI: 1.02–12.03). Conclusion HIV infected patients with renal insufficiency had a higher prevalence of anemia compared to patients with normal renal function. Thus, screening of these patients for anemia and renal insufficiency at base line should be critical not only to reduce mortality but also to improve clinical outcomes.